Self‐Assembling Films of Covalent Organic Frameworks Enable Long‐Term, Efficient Cycling of Zinc‐Ion Batteries. Issue 34 (19th July 2021) - Park, Jun Heuk; Kwak, Myung‐Jun; Hwang, Chihyun; Kang, Kyeong‐Nam; Liu, Nian; Jang, Ji‐Hyun; Grzybowski, Bartosz A.
Abstract: Despite their safety, nontoxicity, and cost‐effectiveness, zinc aqueous batteries still suffer from limited rechargeability and poor cycle life, largely due to spontaneous surface corrosion and formation of large Zn dendrites by irregular and uneven plating and stripping. In this work, these untoward effects are minimized by covering Zn electrodes with ultrathin layers of covalent organic frameworks, COFs. These nanoporous and mechanically flexible films form by self‐assembly—via the straightforward and scalable dip‐coating technique—and permit efficient mass and charge transport while suppressing surface corrosion and growth of large Zn dendrites. The batteries demonstrated have excellent capacity retention and stable polarization voltage for over 420 h of cycling at 1 mA cm −2 . The COF films essential for these improvements can be readily deposited over large areas and curvilinear supports, enabling, for example, foldable wire‐type batteries. Abstract : A straightforward and scalable dip‐coating technique allows for the self‐assembly of ultrathin, flexible, and robust films of covalent organic frameworks (COFs) on Zn electrodes. These COFs prevent inherent electrode corrosion and guide compact Zn deposition, in effect delivering excellent capacity retention and stable polarization voltage (>420 h of cycling at 1 mA cm −2 ) in Zn‐ion batteries, including foldable wire‐type batteries.